Breaking the maternity mold: navigating the return to work and challenging rigid maternal beliefs through an online psychological intervention - Rapisarda, Sebastiano; De Carlo, Alessandro; Pasqualetto, Elena; Volling, Brenda L.; Dal Corso, Laura (Frontiers in Global Women's Health, 2024)
Working mothers must often balance work and family responsibilities which can be affected by rigid and irrational beliefs about motherhood. The present study had two aims: (a) to provide psychometric evidence for a shortened Italian version of the Rigid Maternal Beliefs Scale (RMBS) and (b) to facilitate mothers’ return to work after maternity leave by reducing perceptions of anxiety and stress related to rigid maternal beliefs (i.e., perceptions and societal expectations of mothers, maternal confidence, maternal dichotomy) and by teaching specific recovery strategies (e.g., relaxation, mastery experiences) to manage anxiety and stress through an online psychological intervention. Results replicated the three-factor structure of the original RMBS and showed good psychometric properties. The online psychological intervention resulted in decrease in the rigidity of maternal beliefs, perceived anxiety and stress, and increase in recovery strategies. These initial results are promising and encourage further investigation into online psychological interventions for improving the well-being of working mothers.